Deoxydichlorination of aldehydes catalyzed by Diphenyl sulfoxide - I. A. Gorbunova; D. A. Shipilovskikh; S. A. Shipilovskikh (Chimica Techno Acta)
The diphenyl sulfoxide-catalyzed conversion of aldehydes to 1,1-dichlorides is reported. The reaction proceeds via a sulfurous (IV)-catalysis manifold in which diphenyl sulfoxide turnover is achieved using oxalyl chloride as a consumable reagent.